Does Liability of Newness Matter for Digital Startup on Early Stage of Organizational Life Cycle? - Agus Harijanto; Syamsul Maarif; Herien Puspitawati; Joko Affandi (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
This study aims to test and analyzes the relationship between organizational life cycle characteristics and survivability of a digital startup in the early stage. In establishing new startup and managing early stage, founders have been facing two-fold pages. On one side, the opportunities exploration and exploitation require freedom to acts. On the other side, newly organization faces liability of newness traps that consider organizational formalization and organizational capability. The relationship among aspects is formulated as two-paths mediating roles on the impact of liability of newness and startup survivability. Questionnaires were distributed to 415 respondents in Greater Jakarta City, Indonesia. The study considered Jakarta represented Indonesian digital startup ecosystem. This newly established and still developing startup ecosystem that characterizes the early stages of OLC is considered relevant to the study. The data was analyzed quantitatively using SEM method. The result shows the linkage between the two-paths of mediating role. Since the opportunities are central of mindset for survivability, external legitimacy becomes antecedents of external opportunities as well as reliability and accountability required from organizational formalization and capability. Founders need to understand and translate the impact of liability of newness to establish an appropriate and better organization formalization and organization capability for startup survivability. This study contributes to enrich the early stage of organizational life cycle theory as well as to enhance startup founders’ managerial practices.